Application of nano lignin dispersion liquid, base paper, coating liquid, anti-ultraviolet paper and preparation method
By treating with nano-lignin dispersion, UV-proof paper is prepared, which solves the health and environmental problems of chemical nanomaterials, achieves efficient UV protection and reduces environmental risks.
Patent Information
- Application Number
- CN202511038464.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-09-26
AI Technical Summary
Existing UV-proof eye protection paper uses chemically synthesized nanomaterials, which poses health risks and environmental pollution problems, and is prone to generating hazardous waste during the production process.
Nano-lignin dispersion is used as a bio-based UV shielding material. Alkali lignin or enzymatic lignin is mixed with cationic polymer PDADMAC, and after high-pressure homogenization treatment, it is applied to base paper and coating liquid to prepare UV-proof paper.
It effectively absorbs and reflects ultraviolet rays, reduces environmental accumulation and phototoxicity risks, provides better ultraviolet protection, ensures reading comfort, and avoids the health and environmental problems of chemical materials.
Smart Images

Figure CN120700737A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the application field of lignin, and particularly relates to the application of a nano-lignin dispersion, base paper, coating liquid, UV-proof paper and a preparation method. Background Art
[0002] Ultraviolet rays penetrate the eye from the outside in, damaging the conjunctiva, cornea, lens, and other parts of the eye. Long-term exposure to ultraviolet rays can lead to serious problems such as keratitis and macular degeneration. This damage is difficult to detect in the early stages, but once it occurs, it is irreversible.
[0003] Currently available UV-blocking eye protection films primarily reflect UV rays by adding nanomaterials (such as titanium dioxide and zinc oxide). For example, some patented technologies utilize nanomaterials like cerium oxide and aluminum oxide. However, these chemically synthesized nanomaterials may pose health risks (such as skin irritation and environmental pollution), and their production process can easily generate hazardous waste. Summary of the Invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an application of a nano-lignin dispersion, a base paper, a coating liquid, an anti-ultraviolet paper and a preparation method.
[0005] To achieve the above object, the technical solution adopted by the present invention is: A nano-lignin dispersion is used for coating liquid and / or base paper. The nano-lignin dispersion is prepared by the following method: alkali lignin or enzymatic lignin is dispersed, a cationic polymer is added, and high-pressure homogenization is performed to obtain the dispersion.
[0006] High pressure homogenization is carried out in two steps: the first step is 60 MPa, homogenization is performed twice; the second step is 100 MPa, homogenization is performed 4-15 times; the cationic polymer is PDADMAC The present invention also includes a method for preparing base paper containing nano-lignin, comprising the following steps: preparing wood pulp, filler and the nano-lignin dispersion into a slurry, and papermaking to obtain UV-proof eye-protecting base paper containing nano-lignin; the absolute dry weight of lignin added to the nano-lignin dispersion is 1‰-8‰ of the absolute dry weight of the wood pulp.
[0007] The wood pulp is a mixture of coniferous wood pulp, broadleaf wood pulp and high-yield pulp; the absolute dry weight ratio of the coniferous wood pulp, broadleaf wood pulp and high-yield pulp is 6.5:3.5:0.5.
[0008] The filler is light calcium carbonate PCC; the content of the PCC in the slurry is 10%.
[0009] The present invention also includes a base paper containing nano-lignin obtained by the preparation method.
[0010] The present invention also includes a coating liquid containing nano-lignin, which includes the nano-lignin dispersion and a functional additive; the functional additive is at least one of polyvinyl alcohol (PVA), methyl cellulose, carboxymethyl cellulose, starch, oxidized starch, and carboxymethyl starch.
[0011] The absolute dry weight ratio of the nano-lignin dispersion to the functional additive is (1-2):100.
[0012] The present invention also includes an anti-ultraviolet paper, comprising a substrate and a coating; the substrate comprises white paper or the nano-lignin-containing base paper; the coating is obtained by coating the nano-lignin-containing coating liquid onto the substrate.
[0013] The present invention also includes a method for preparing the anti-ultraviolet paper, comprising the following steps: applying the coating liquid onto a substrate to obtain a coating; the loading amount of the coating liquid solid content on the substrate is 1-10 g / m 2 .
[0014] Compared with the prior art, the present invention has the following beneficial effects: Lignin is the second most abundant natural polymer. The phenylpropane in lignin contains conjugated double bonds and phenolic hydroxyl groups that absorb ultraviolet light. As a naturally renewable material, lignin is non-toxic and biodegradable. The technical solution of this application incorporates nano-lignin as a bio-based UV shielding material to replace traditional chemical UV absorbers, effectively reducing environmental accumulation and phototoxicity risks. The addition of lignin provides enhanced protection and absorption in the ultraviolet region, reducing eye damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The UV transmittance of the nano-lignin contents homogenized 12 times were 1‰, 3‰, 5‰, and 8‰ respectively; Figure 2 The UV transmittance of the nano-lignin contents was 1‰, 3‰, 5‰, and 8‰ after homogenization for 15 times; Figure 3 The UV transmittance of the nano-lignin with a content of 8‰ homogenized for 4, 6, 9, 12, and 15 times; Figure 4 The UV transmittance of nano-lignin / PVA with the contents of 1%, 1.5% and 2% were obtained by homogenization 15 times.
[0016] Figure 5 The contents of nano-lignin / PVA homogenized 15 times were 1%, 1.5%, and 2% respectively, and the UV transmittance of the base paper. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and the best embodiments.
[0018] Alkali lignin, softwood pulp, hardwood pulp, and high-yield pulp were purchased from Hunan Juntai New Materials Technology Co., Ltd. Polyvinyl alcohol, light calcium carbonate PCC, and dimethyldiallyl ammonium chloride homopolymer PDADMAC were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0019] Example 1: A method for preparing a base paper containing nano-lignin, comprising the following steps: 1. Preparation of Nanolignin Dispersion: In this example, alkali lignin was mechanically ground and passed through a 200-mesh sieve to obtain a lignin powder. Water was added to prepare a 5% wt lignin suspension. The suspension was homogenized twice at a pressure of 60 MPa. PDADMAC was added at an amount of 10% of the absolute dry weight of the lignin. After mixing, the suspension was homogenized 12 times at a pressure of 100 MPa to obtain a nanolignin dispersion.
[0020] 2. Preparation of base paper containing nano-lignin: the papermaking weight is 80g / cm 3 The round paper is made of a mixture of softwood pulp, hardwood pulp, and high-yield pulp; the dry weight ratios of softwood pulp, hardwood pulp, and high-yield pulp are 6.5:3.5:0.5, respectively. Specifically, in this embodiment, a nano-lignin dispersion was added to 0.2512 g of PCC (the PCC content in the slurry was 10%), 6.91 g of softwood pulp, 3.97 g of hardwood pulp, and 0.11 g of high-yield pulp, and the mixture was then uniformly mixed and water was added to form a slurry. The slurry was then sheeted using a rapid paper former to produce UV-protective eye-protection paper.
[0021] Among them, the addition amount of nano-lignin (absolute dry weight) is 1‰, 3‰, 5‰ and 8‰ of the absolute dry weight of wood pulp respectively.
[0022] Figure 1 The following is a comparison chart of the absorbance curves of different added amounts of nano-lignin in the full band of 200-800nm ultraviolet visible light. The results show that nano-lignin can effectively reduce ultraviolet light, and the higher the lignin content, the better the ultraviolet blocking effect. Compared with white paper, white paper does not have anti-ultraviolet function. Table 1 compares the whiteness of base paper containing nano-lignin and white paper. The reduction in whiteness after aging for 6 hours under a 300W, 360-365nm wavelength ultraviolet lamp is significantly lower than that of ordinary white paper. The average ultraviolet reflectivity of white paper as a control example is 36.45%. After homogenization 12 times, the reflectivities of anti-ultraviolet eye-protection paper containing 1‰, 3‰, 5‰, and 8‰ nano-lignin are 35.23%, 34.61%, 34.33%, and 29.56%, respectively.
[0023] Table 1
[0024] Example 2: A method for preparing a base paper containing nano-lignin, comprising the following steps: 1. Preparation of Nanolignin Dispersion: In this example, alkali lignin was mechanically ground and passed through a 200-mesh sieve to obtain a lignin powder. Water was added to prepare a 5% wt lignin suspension. The suspension was homogenized twice at a pressure of 60 MPa. PDADMAC was added at an amount of 10% of the absolute dry weight of the lignin. After mixing, the suspension was homogenized 15 times at a pressure of 100 MPa to obtain a nanolignin dispersion.
[0025] 2. The preparation of base paper containing nano-lignin is the same as that in Example 1.
[0026] Figure 2 The following is a comparison chart of the absorbance curves of lignin with different addition amounts in the full band of 200-800nm ultraviolet visible light. The results show that lignin can effectively reduce ultraviolet light, and the higher the lignin content, the better the ultraviolet blocking effect. Compared with white paper, it does not have anti-ultraviolet function. Table 2 compares the whiteness of base paper containing nano-lignin and white paper. The reduction in whiteness after aging for 6 hours under 300W, 360-365nm wavelength ultraviolet light is significantly lower than that of ordinary white paper. The average ultraviolet reflectivity of white paper is 36.45%. After homogenization 15 times, the reflectivity of anti-ultraviolet eye protection paper containing 1‰, 3‰, 5‰, and 8‰ nano-lignin are 33.49%, 31.31%, 30.57%, and 27.58%, respectively.
[0027] Table 2
[0028] Example 3: A method for preparing a base paper containing nano-lignin, comprising the following steps: 1. Preparation of Nano-lignin Dispersion: In this example, alkali lignin was mechanically ground and passed through a 200-mesh sieve to obtain a lignin powder. Water was added to prepare a 5% wt lignin suspension. The suspension was homogenized twice at a pressure of 60 MPa. PDADMAC was added in an amount corresponding to 10% of the absolute dry weight of the lignin. After mixing, the suspension was homogenized at a pressure of 100 MPa for 4, 6, 9, 12, and 15 times, respectively, to obtain a nano-lignin dispersion.
[0029] 2. Preparation of base paper containing nano-lignin: the paper weight is 80g / cm 3For round paper, the ratios of softwood pulp, hardwood pulp, and high-yield pulp are 6.5:3.5:0.5, respectively. 0.2512g of PCC, 6.91g of softwood pulp, 3.97g of hardwood pulp, and 0.11g of high-yield pulp are added to the nano-lignin dispersion, mixed evenly, and then water is added to form a slurry. This slurry is then passed through a rapid sheet former to create UV-protective eye-protection paper. The nano-lignin (absolute dry weight) is added at 8‰ of the absolute dry weight of the wood pulp.
[0030] Figure 3 The present invention is a reflectivity curve comparison diagram of the full-band ultraviolet-visible light of 200-800nm. The anti-ultraviolet eye-protection paper in the present invention significantly reduces the reflectivity of the eye-damaging light in the ultraviolet light zone (200-400nm) and the harmful blue-violet light zone (400-480nm). At the same time, the reflectivity of the light of 500-700nm, which is comfortable for the human eye to read, is basically unchanged. By comparing the whiteness of the paper containing nano-lignin and white paper with different homogenization times, along with the increase of the homogenization times, the reflectivity of the paper to the ultraviolet-visible light decreases, which can prove that the homogenization times have a great impact on the reflectivity of the ultraviolet-visible light. Therefore, the anti-ultraviolet eye-protection paper produced by the present invention can reduce the ultraviolet region reflectivity, while also ensuring the comfort of reading, and the effect is better than most white paper available on the market.
[0031] Table 3
[0032] Example 4: Preparation of UV-proof paper; In this example, a coating liquid containing nano-lignin is coated on ordinary white paper by a paper coating method.
[0033] 1. Preparation of Nano-lignin Dispersion: Alkali lignin was mechanically ground and passed through a 200-mesh sieve to obtain lignin powder. Water was added to prepare a 5% wt lignin suspension. The suspension was homogenized twice at 60 MPa. PDADMAC was added at an amount equivalent to 10% of the absolute dry weight of the lignin. After mixing, the suspension was homogenized 15 times at 100 MPa to obtain a nano-lignin dispersion. 2. Preparation of a coating liquid containing nano-lignin: Use a high-speed disperser to disperse 0.065 g of a nano-lignin dispersion (the dry weight ratio of nano-lignin to the functional additive PVA is 1:100), 0.0975 g of a nano-lignin dispersion (the dry weight ratio of nano-lignin to the functional additive PVA is 1.5:100), and 0.13 g (the dry weight ratio of nano-lignin to the functional additive PVA is 2:100) of a nano-lignin dispersion (absolute dry weight) into 100 g of a PVA solution with a concentration of 6.5% to prepare a coating liquid containing nano-lignin; 3. Preparation of UV-proof paper: Use rod coating to apply the prepared nano-lignin coating liquid on ordinary white paper with a coating amount of 4g / m 2 , and after drying, you can get the anti-ultraviolet eye protection paper.
[0034] Figure 4 Comparison of reflectivity curves of different coating amounts of nano-lignin in the full band of 200-800nm ultraviolet visible light. The results show that nano-lignin can effectively reduce the reflectivity of ultraviolet light. The higher the lignin content, the better the ultraviolet blocking effect. Compared with the white paper on the market, it does not have anti-ultraviolet function. Table 4 compares the whiteness of paper containing nano-lignin and white paper. The reduction in whiteness after aging for 6 hours under a 300W, 360-365nm wavelength ultraviolet lamp is significantly lower than that of ordinary white paper. The average ultraviolet reflectivity of white paper is 36.45%. After homogenization 15 times, the reflectivity of anti-ultraviolet eye-protection paper containing 1%, 1.5%, and 2% nano-lignin / PVA content are 27.53%, 26.29%, and 24.94%, respectively.
[0035] Table 4
[0036] Example 5: Preparation of UV-proof paper; In this example, a coating liquid containing nano-lignin is applied to the base paper containing nano-lignin obtained in Example 1 (homogenized 12 times in Example 1, with a nano-lignin concentration of 5‰) by coating paper.
[0037] 1. Preparation of Nano-lignin Dispersion: Alkali lignin was mechanically ground and passed through a 200-mesh sieve to obtain lignin powder. Water was added to prepare a 5% wt lignin suspension. The suspension was homogenized twice at a pressure of 60 MPa. PDADMAC was added at an amount corresponding to 10% of the lignin content. After mixing, the suspension was homogenized 15 times at a pressure of 100 MPa to obtain a nano-lignin dispersion. 2. Preparation of a coating liquid containing nano-lignin: Use a high-speed disperser to disperse 0.065 g of nano-lignin dispersion (the dry weight ratio of nano-lignin to functional additives is 1:100), 0.0975 g of nano-lignin dispersion (the dry weight ratio of nano-lignin to functional additive PVA is 1.5:100), and 0.13 g (the dry weight ratio of nano-lignin to functional additive PVA is 2:10) of nano-lignin dispersion (absolute dry weight) into 100 g of PVA solution with a concentration of 6.5% to prepare a coating liquid containing nano-lignin; 3. Preparation of base paper containing nano-lignin: the papermaking weight is 80g / cm 3The round paper is made of a mixture of softwood pulp, hardwood pulp, and high-yield pulp; the dry weight ratios of softwood pulp, hardwood pulp, and high-yield pulp are 6.5:3.5:0.5, respectively. Specifically, in this example, a nanolignin dispersion (the nanolignin concentration of 5‰ obtained by homogenizing 12 times as described in Example 1) was added to 0.2512g of PCC, 6.91g of softwood pulp, 3.97g of hardwood pulp, and 0.11g of high-yield pulp. The mixture was then uniformly mixed and water was added to form a slurry. The slurry was then sheeted using a rapid paper former to produce UV-protective eye-protection paper. The amount of nanolignin added (dry weight) corresponded to 5‰ of the dry weight of the wood pulp.
[0038] 4. Preparation of UV-proof paper: Use a rod coater to coat the nano-lignin coating solution prepared in step 2) on the base paper obtained in step 3, with a coating amount of 4 g / m 2 , and after drying, you can get the anti-ultraviolet eye protection paper.
[0039] Figure 5 Comparison of reflectivity curves of nano-lignin with different coating amounts in the full band of 200-800nm ultraviolet and visible light. The results show that nano-lignin can effectively reduce the reflectivity of ultraviolet light. The higher the lignin content, the better the ultraviolet blocking effect. By comparing with the comparative base paper (the nano-lignin concentration of 5‰ homogenized 12 times in Example 1), it can be seen that the anti-ultraviolet effect of the paper can be enhanced after nano-lignin is coated on the paper. Table 5 compares the whiteness of the paper containing nano-lignin with that of white paper. The reduction in whiteness after aging for 6 hours under a 300W, 360-365nm wavelength ultraviolet lamp is significantly lower than that of the base paper. The average ultraviolet reflectivity of the comparative base paper is 34.33%. The reflectivity of the anti-ultraviolet eye-protection paper containing 1%, 1.5%, and 2% nano-lignin / PVA content after homogenization 15 times are 26.31%, 25.79%, and 22.57%, respectively.
[0040] Table 5
[0041] In summary, lignin is the second most abundant natural polymer in nature. The phenylpropane in lignin contains conjugated double bonds and phenolic hydroxyl groups that can absorb ultraviolet light. As a natural renewable material, lignin is non-toxic and biodegradable. The technical solution of this application uses lignin as a bio-based ultraviolet shielding material to replace traditional chemical ultraviolet absorbers, which can effectively reduce environmental accumulation and phototoxicity risks. The addition of lignin can provide better protection and absorption effects in the ultraviolet region, reducing damage to the human eye.
[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. An application of a nano-lignin dispersion, characterized in that: Applicable to coating liquid and / or base paper; the nano-lignin dispersion is prepared by the following method: after dispersing alkali lignin or enzymatic lignin, a cationic polymer is added and the mixture is homogenized under high pressure.
2. The use of the nano-lignin dispersion according to claim 1, characterized in that The high-pressure homogenization is carried out in two steps: the first step is 60 MPa, homogenization is performed twice; the second step is 100 MPa, homogenization is performed 4-15 times; the cationic polymer is PDADMAC.
3. A method for preparing base paper containing nano-lignin, characterized in that: The method comprises the following steps: preparing wood pulp, filler and the nano-lignin dispersion according to claim 1 or 2 into slurry, and papermaking the anti-ultraviolet eye-protection base paper containing nano-lignin; the absolute dry weight of lignin added to the nano-lignin dispersion is 1‰-8‰ of the absolute dry weight of the wood pulp.
4. The method for preparing base paper containing nano-lignin according to claim 3, characterized in that: The wood pulp is a mixture of coniferous wood pulp, broadleaf wood pulp and high-yield pulp; the absolute dry weight ratio of the coniferous wood pulp, broadleaf wood pulp and high-yield pulp is 6.5:3.5:0.
5.
5. The method for preparing base paper containing nano-lignin according to claim 3, characterized in that: The filler is light calcium carbonate PCC; the content of the PCC in the slurry is 10%.
6. A base paper containing nano-lignin obtained by the preparation method according to any one of claims 3 to 5.
7. A coating liquid containing nano-lignin, characterized in that, The invention comprises the nano-lignin dispersion according to claim 1 or 2 and a functional additive; the functional additive is at least one of polyvinyl alcohol (PVA), methyl cellulose, carboxymethyl cellulose, starch, oxidized starch and carboxymethyl starch.
8. The coating liquid containing nano-lignin according to claim 7, characterized in that The dry weight ratio of the nano-lignin dispersion to the functional additive is (1-2):
100. 9.An anti-ultraviolet paper, characterized in that: It comprises a substrate and a coating; the substrate comprises white paper or the nano-lignin-containing base paper according to claim 6; the coating is obtained by applying the nano-lignin-containing coating liquid according to claim 7 or 8 onto the substrate.
10. A method for preparing the anti-ultraviolet paper according to claim 9, characterized in that: The method comprises the following steps: applying the coating liquid to a substrate; the loading amount of the coating liquid solid content on the substrate is 1-10 g / m 2 .